Evaluation of Rapid Reaction Unit Policies for Handling Extreme Poverty, Inflation and Stunting in Harmony in Efforts to Reduce Stunting Rates in North Konawe Regency - Risky, Sartini; Nofitasari, Ari; Asbath, Asbath; Islaeli, Islaeli (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Stunting is a chronic nutritional problem in children. The prevalence of stunting in the North Konawe District Health Service area in 2022 will be 21.6% and in 2023 it will be 25.6%. One of the public policy steps taken by the North Konawe Regency Government is the implementation of the URC KISS program, but it has never been evaluated effectively. The aim of the research is to evaluate the rapid response unit's policies for handling extreme poverty, inflation and stunting in harmony with efforts to reduce stunting rates. Methods: The type of research is qualitative research, case study design. The subjects in this research were 12 people consisting of 2 key informants and 10 ordinary informants. Sampling technique using the Snowball Sampling. Data analysis, by analyse the data reduction stages, data display and drawing conclusions. Results: The results of the research on the evaluation of financing input were funded directly from the regional government, available human resources and according to their competence, available infrastructure in the form of cars, motorbikes and anthropometric measuring equipment. And accompanied by guidelines for efforts to reduce stunting rates in North Konawe Regency. Then the planning process implemented is to collect family card data, organization is structured and implementation is by providing additional food and groceries. Then monitoring the toddler's height every week is carried out. Output is in the form of providing additional food and foods such as oil, eggs. The outcome is that the prevalence of stunting will decrease, namely in 2023 it will be 6% and in 2024 it will be 5.4%. Conclusion: Input evaluation available as needed. The process was carried out well. The output was implemented by providing local supplementary food and the outcome was that the prevalence of stunting reached 5.4%.